2008
DOI: 10.1016/j.cryogenics.2008.04.003
|View full text |Cite
|
Sign up to set email alerts
|

State of the art powder-in-tube niobium–tin superconductors

Abstract: Powder-in-Tube (PIT) processed Niobium-Tin wires are commercially manufactured for nearly three decades and have demonstrated a combination of very high current density (presently up to 2500 Amm -2 non-Cu at 12 T and 4.2 K) with fine (35 /im), well separated filaments. We review the developments that have led to the present state of the art PIT Niobium-Tin wires, discuss the wire manufacturing and A15 formation processes, and describe typical superconducting performance in relation to magnetic field and strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…The slope dβ/dx computed from linear fits in the fine grain region of the data obtained from EDX and AC magnetometry is 0.11 at.%/µm in both cases, in agreement with results obtained by others in similar studies on PIT wires. 5,9,10 In section II A we state that the introduction of an intra-granular Sn gradient is necessary to achieve agreement between the histogram obtained from the AC magnetometry method and the actual calorimetry data. One might therefore argue that the method is only useful if the intra-granular Sn gradient or the calorimetry histogram is known.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The slope dβ/dx computed from linear fits in the fine grain region of the data obtained from EDX and AC magnetometry is 0.11 at.%/µm in both cases, in agreement with results obtained by others in similar studies on PIT wires. 5,9,10 In section II A we state that the introduction of an intra-granular Sn gradient is necessary to achieve agreement between the histogram obtained from the AC magnetometry method and the actual calorimetry data. One might therefore argue that the method is only useful if the intra-granular Sn gradient or the calorimetry histogram is known.…”
Section: Resultsmentioning
confidence: 99%
“…This gradient is sensitive to the reaction temperature and duration, and, given a sensible choice for the heat treatment, takes on values of typically 0.1 -0.4 at.%/µm. 5,9,10 Another characteristic feature of PIT Nb 3 Sn wires is their twofold grain morphology: the sub-elements consist of fine grains (∼ 150 nm) on the outside, whereas large grains (∼ 1 -2 µm) dominate near the core. It was found that these two grain types exhibit significantly different T c and B c2 distributions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general idea of tube type conductors, where Cu and Sn are inserted into Nb tubes, has been pursued before [7][8][9][10][11], and these conductors do have some similarities to powderin-tube (PIT) strands (as well as differences) [12][13][14][15][16][17][18][19][20][21]. Early on, geometrically similar conductors were fabricated by Murase and associates [7].…”
Section: Introductionmentioning
confidence: 99%